Analisis Pengaruh Intensitas Pencahayaan Di Laboratorium Pengujian Terhadap Akurasi Pengujian - Tri Ernita; Rachman, Boby; Yulius, Henny; Sastri (Politeknik ATI Padang, 2025)
The testing laboratory is a high-precision testing room that reguires adeguate environmental conditions for testing needs.As a testing laboratory, it is important for the banten Indonesia Laboratory to control the laboratory's environmental conditions, one of which is lighting intensity.Inadeguate lighting intensity can reduce testing accuracy, Currently, the average lighting intensity in the banten Indonesia Laboratory is 370 lux, this value is below the regulatory standard Threshold value, which according to PERMENKES NO. 70 of 2016 for standard laboratories lighting intensity is 500 lux. This study aims to increase lighting according to SNI 7062:2019 and testing accuracy in the Banten Indonesia Laboratory and to determine how strong the relationship betwen lighting intensity and testing accuracy is using correlation analysis with SPSS V.27. The results of this study indicate that lighting intensity has increased to 489 lux and the average accuracy has increased by 7.5 % after changing the lamp,in addition,the relationship between lighting intensity and testing accuracy strong ,this is evidenced by the result of the correlation analysis obtained a significance value of 0.620 and 0.627 .